Pengembangan variasi model latihan Resistance band untuk meningkatkan kecepatan pukulan jab-straight pada atlet muay thai provinsi gorontalo - Fadlun Ch. Anwar; Kadir, Suprianto; Meri Haryani; Palakum, Agrilan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop variations of resistance band training models to improve the speed of jab-straight punches in Muay Thai athletes in Gorontalo Province. This study uses the research and development method. The sample in this study consisted of 5 female Muay Thai athletes from Gorontalo Province. The research instruments used equipment such as a punching bag and stopwatch to measure rapid punches performed for 30 seconds. The results of the study show that the developed resistance band training model falls into the very valid category based on validation by material and media experts. The implementation of the training model shows an increase in the speed of jab-straight punches in athletes after participating in the training program. Thus, the developed resistance band training model is declared valid and effective as an alternative exercise to improve the speed of jab-straight punches in Muay Thai athletes in Gorontalo Province.